JAMES AND SCRIPTURE: AN EXERCISE IN INTERTEXTUALITY - Popkes, Wiard (New Testament studies, 1999)
The epistle contains three OT quotations as well as several biblical allusions and examples; other sources (such as Ben Sira) are not discernible. James collected excerpt-material from a wide background, not just by oral tradition – hence ‘intertextuality’. In a similar way the OT quotations, all combative in nature, seem to have been taken from secondary sources, viz. from Pauline (ch. 2) and ‘Petrine’ (ch. 4) traditions. Probably James had no direct access to a full OT text or longer parts of it. Nevertheless he uses ‘scripture’ as an authority and may have had a concept of canon.